2020
DOI: 10.1002/hbm.25287
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of functional brain network architecture in chronic osteoarthritis pain

Abstract: Osteoarthritis (OA) manifests with chronic pain, motor impairment, and proprioceptive changes. However, the role of the brain in the disease is largely unknown. Here, we studied brain networks using the mathematical properties of graphs in a large sample of knee and hip OA (KOA, n = 91; HOA, n = 23) patients. We used a robust validation strategy by subdividing the KOA data into discovery and testing groups and tested the generalizability of our findings in HOA. Despite brain global topological properties being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 48 publications
6
53
0
Order By: Relevance
“…Also, considering that subcortical structures, such as the thalamus, are important for the early processing of nociceptive signals from the peripheral nervous system, our finding suggests that the recruitment of both bottom-up (subcortical) and top-down (frontoparietal) systems and their integration are crucial to the conscious experience of sustained pain. Previous studies that reported modular reorganization of the somatomotor network (H Mano et al, 2018) and frontoparietal network (Barroso et al, 2021;H Mano et al, 2018) in chronic pain are also in line with our results. Importantly, this systems-level integration occurred in a somatotopy-specific way-the SVM classifier (Figure 4) showed that the ventral primary somatomotor area, which subserves tongue sensation, was segregated from the other somatomotor regions and integrated with the subcortical regions during the early period of pain.…”
Section: Discussionsupporting
confidence: 93%
“…Also, considering that subcortical structures, such as the thalamus, are important for the early processing of nociceptive signals from the peripheral nervous system, our finding suggests that the recruitment of both bottom-up (subcortical) and top-down (frontoparietal) systems and their integration are crucial to the conscious experience of sustained pain. Previous studies that reported modular reorganization of the somatomotor network (H Mano et al, 2018) and frontoparietal network (Barroso et al, 2021;H Mano et al, 2018) in chronic pain are also in line with our results. Importantly, this systems-level integration occurred in a somatotopy-specific way-the SVM classifier (Figure 4) showed that the ventral primary somatomotor area, which subserves tongue sensation, was segregated from the other somatomotor regions and integrated with the subcortical regions during the early period of pain.…”
Section: Discussionsupporting
confidence: 93%
“…The left parahippocampal cortex is one of the hubs in gout patients group discovered in this study. Similar results were reported in previous studies on the functional brain network of osteoarthritis, in a region that was thought to be related to the response to analgesics ( 56 , 57 ). The insular cortex is considered essential for the perception, modulation, and chronification of pain ( 58 ).…”
Section: Discussionsupporting
confidence: 91%
“…The anterior cingulate cortex is a region involved in executive, attention, and decisionmaking processes [52]. Previous studies have reported a direct association between the presence of chronic pain and linked memory loss in this area [39,53,54]. In our pain model, an increased expression of PI3K was observed in the anterior cingulate cortex, which was only reversed by GYY4137 treatment.…”
Section: Discussionmentioning
confidence: 51%